Age at menarche of university students in Bangladesh: secular trends and association with adult anthropometric measures and socio-demographic factors - Hossain, M.D.G.; Islam, S.; Aik, S.A.W.; Zaman, T.K.; Lestrel, P.E. (Cambridge University Press, 2010)
Age at menarche has been shown to be an important indicator for diseases such as breast cancer and ischaemic heart disease. The aim of the present study was to document secular trends in age at menarche and their association with anthropometric measures and socio-demographic factors in university students in Bangladesh. Data were collected from 995 students from Rajshahi University using a stratified sampling technique between July 2004 and May 2005. Trends in age at menarche were examined by linear regression analysis. Multiple regression analysis was used to assess the association of age at menarche with adult anthropometric measures and various socio-demographic factors. The mean and median age of menarche were 13.12+/-1.16 and 13.17 years, respectively, with an increasing tendency among birth-year cohorts from 1979 to 1986. Menarcheal age was negatively associated with BMI (p<0.01), but positively associated with height (p<0.05). Early menarche was especially pronounced among students from urban environments, Muslims and those with better educated mothers. Increasing age at menarche may be explained by improved nutritional status among Bangladeshi populations. Early menarche was associated with residence location at adolescence, religion and mother's education.